الحبكة الفنية في مسرحية "الطالب المغتر" لإبراهيم ليري أمين - Alhajj Yahuza, Muhammad Yahuza; Ali Abdulkadir Al'Asaly (Nady Al-Adab : Jurnal Bahasa Arab, 2025)
الملخص حاولت الدراسة الكشف عن الحبكة الفنية في مسرحية "الطالب المغتر" بعنوان (الحبكة الفنية في مسرحية الطالب المغتر، لإبراهيم ليري أمين، دراسة تحليلية) وذلك لأهميتها في ربط الأحداث المتسلسلة في القصة، مع التأكيد على علاقة وطيدة بين الأحداث بعضها، من أجل توليد أثر عاطفي أو فني لدى المتلقي، وقد حاولت الدراسة تتابع سبر التزام بالحبكة الفنية وتوظيفها، وذلك أن بعض الكتاب والدارسين لم يعطيها اهتماما بالغا يليق بها عند توظيفها في بعض الأعمال، لذا أراد الباحث دراستها عن طريق تحليلها، كما استخدمت المنهج التحليلي، بغية الوصول إلى الإجابة عن الأسئلة التالية: ما الحبكة الفنية في المسرحية؟ وما مدى التزام الكاتب بتقنيتها؟ وما المحتوى الفكري والثقافي والاجتماعي التي أدّتها؟. ويقتصر حدود البحث في الكشف عن الحبكة الفنية في مسرحية "الطالب المغتر" دون غيرها من العناصر، وتوصلت إلى نتائج أهمها: أن السارد وفق في الالتزام بالحبكة الفنية، بحيث تتابع تسلسلها تدريجياًّ حتى وصل إلى الحل الناجع، دون تسرع مخل، ولا تدرج ممل، وهذا مما زاد للعمل قيمة. الكلمات المفتاحية: الحبكة الفنية؛ المسرحية العربية؛ نيجيريا؛ الطالب المغتر. Abstract The study aimed to explore the artistic plot in the play "The Arrogant Student," titled "The Artistic Plot in 'ADDALIBUL-MUGTAR' by Ibrahim Lere Amin: An Analytical Study." This is significant as it links the sequential events of the story, emphasizing the close relationship between these events to create an emotional or artistic impact on the audience. The study also sought to follow the commitment to the artistic plot and its application, as some writers and scholars have not given it the attention it deserves when employed in certain works. Therefore, the researcher aimed to analyze it. The analytical approach was used to answer the following questions: What is the artistic plot in the play? How committed is the writer to its technique? And what intellectual, cultural, and social content does it convey? The scope of the research is limited to revealing the artistic plot in the play "ADDALIBUL-MUGTAR" without delving into other elements. The study concluded with several findings, the most important of which is that the narrator succeeded in adhering to the artistic plot, maintaining a gradual sequence leading to a successful resolution, without rushing or dragging, which enhanced the value of the work. Keywords:  Artistic Plot; The Nigerian; Arabic Play; The Arrogant Student.